A high-rate sodium iron phosphate positive electrode material and preparation method

Through infrared thermal imaging technology, the solid phase sintering reaction of sodium iron phosphate positive electrode material is monitored, the conduction block coefficient and sufficient coefficient are calculated, and the adaptive adjustment of the reaction time is achieved, which solves the limitations of the material in cycle stability and rate performance. , improves the overall performance of the material.

CN118405680BActive Publication Date: 2025-02-11兴荣新源(厦门)科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410489912.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-23
Publication Date
2025-02-11
Estimated Expiration
2044-04-23

AI Technical Summary

Technical Problem

The sodium ion battery prepared by sodium ferric phosphate as a positive electrode material has limitations in cycle stability and rate performance, and there is a problem of excessive sintering or insufficient reaction in the control of the solid phase sintering reaction time.

Method used

By collecting infrared thermal imaging images during the solid phase sintering reaction, building a cell window and calculating the conduction block coefficient and solid phase sintering sufficient coefficient, adaptive adjustment of the reaction time of solid phase sintering reaction is achieved.

Benefits of technology

The cycling performance and rate performance of the titanium-based fast ion conductor modified sodium ferrophosphate cathode material is improved, and performance degradation caused by excessive or short solid phase sintering reaction time is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118405680B_ABST
    Figure CN118405680B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of electrode positive material preparation, and specifically to a high-rate sodium iron phosphate positive electrode material and a preparation method, the method comprising: dissolving PEG-6000 flaky particles in ultrapure water, stirring and sequentially adding iron phosphate, anatase titanium dioxide, sodium dihydrogen phosphate, and sodium carbonate powder to obtain a mixed solution, grinding the mixed solution to obtain a mixed slurry, spray drying the mixed slurry, solid-phase sintering reaction, and refining treatment to obtain a titanium-based fast ion conductor modified sodium iron phosphate positive electrode material, collecting solid-phase sintering infrared thermal imaging images at each moment during the solid-phase sintering reaction, and completing the adaptive adjustment of the solid-phase sintering reaction time according to the solid-phase sintering sufficient coefficient of each sintering interval. The present invention aims to adjust the solid-phase sintering reaction time and improve the cycle performance and rate performance of the sodium iron phosphate positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode positive electrode material preparation, and in particular to a high-rate sodium iron phosphate positive electrode material and a preparation method thereof. Background Art

[0002] Sodium is an element with high abundance in the earth's crust. Compared with lithium resources, sodium resources are more widely distributed, and sodium-ion batteries have become a strong competitor for large-scale energy storage applications. Sodium iron phosphate, as a non-toxic positive electrode material, is environmentally friendly and in line with the current battery industry's pursuit of green and sustainable technologies. Sodium-ion batteries prepared using sodium iron phosphate as a positive electrode material are more stable under overcharge and high temperature conditions and have lower costs. However, sodium-ion batteries prepared using sodium iron phosphate as a positive electrode material have certain limitations in cycle stability and rate performance.

[0003] Titanium-based fast ion conductor modified sodium iron phosphate positive electrode material can maintain the high capacity characteristics of sodium iron phosphate and has the high rate characteristics of titanium-based fast ion conductor materials. However, in the preparation process of titanium-based fast ion conductor modified sodium iron phosphate positive electrode material, the solid phase sintering reaction time needs to be strictly controlled. When the solid phase sintering reaction time is too long, it may cause excessive sintering of the material, affecting the ion conductivity of the titanium-based fast ion conductor, and may also affect the cycle life of the material; when the solid phase sintering reaction time is too short, the raw materials may not react fully, resulting in poor consistency and uniformity of the material, which in turn affects the rate performance of the material. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a high-rate sodium iron phosphate positive electrode material and a preparation method. The technical scheme adopted is as follows:

[0005] In a first aspect, an embodiment of the present invention provides a method for preparing a high-rate sodium iron phosphate positive electrode material, the method comprising the following steps:

[0006] (1) dissolving PEG-6000 flake particles in ultrapure water, stirring, and sequentially adding iron phosphate, anatase titanium dioxide, sodium dihydrogen phosphate, and sodium carbonate powder to obtain a mixed solution;

[0007] (2) the mixed solution was sheared and dispersed at 1000 rpm for 30 min, and then transferred to a sand mill for grinding to obtain a mixed slurry;

[0008] (3) spray drying the mixed slurry, and then placing it in a nitrogen-protected box furnace for solid-phase sintering reaction, and after the reaction product is cooled, refining treatment is performed to obtain a titanium-based fast ion conductor modified sodium iron phosphate positive electrode material; collecting solid-phase sintering infrared thermal imaging images at each moment in the solid-phase sintering reaction process; constructing a pixel window with each pixel in the image as the center; obtaining the conduction resistance coefficient of each pixel window according to the distribution characteristics of the temperature value of each pixel in each pixel window; evenly dividing the solid-phase sintering reaction process into various sintering intervals; obtaining the solid-phase sintering sufficiency coefficient of each sintering interval according to the conduction resistance coefficient of each pixel window and the temperature change characteristics of the pixels at different times in each sintering interval; and completing the adaptive adjustment of the solid-phase sintering reaction time according to the solid-phase sufficiency coefficient of each sintering interval.

[0009] Preferably, in the process of obtaining the mixed solution, the mass ratio of PEG-6000, ultrapure water, iron phosphate, anatase titanium dioxide, sodium dihydrogen phosphate, and sodium carbonate powder is 1:62.5:23.57:0.32:0.725:8.53.

[0010] Preferably, the grinding medium is a zirconia ball with a diameter of 0.1-0.2 mm, the grinding linear speed is 15 m / s, the grinding time is 4 h, and a mixed slurry with a median particle size D50 of 80-200 nm is obtained.

[0011] Preferably, the spray drying comprises:

[0012] The feed inlet temperature is 240°C, the discharge port temperature is 100°C, and the median particle size of the spray particles is 6-8 μm.

[0013] Preferably, the solid phase sintering reaction comprises: solid phase sintering at 800° C. for 8-12 hours, and the temperature rising rate during the solid phase sintering reaction is 2° C. / min.

[0014] Preferably, the refinement treatment is to pass through a 150-mesh sieve, and the specific surface area of ​​the titanium-based fast ion conductor modified sodium iron phosphate positive electrode material is 7.65 m 2 / g, median particle size is 7-9μm, tap density is 1.2g / cm 3 .

[0015] Preferably, obtaining the conduction resistance coefficient of each pixel window according to the distribution characteristics of the temperature value of each pixel in each pixel window includes:

[0016] Arrange the temperature values ​​of all pixels in each pixel window in ascending order as the temperature sequence of each pixel window, take the pixels in the pixel window whose temperature values ​​are greater than or equal to the third quartile of the temperature sequence as the high-temperature pixels of the pixel window, take the mean value of all high-temperature pixels in each pixel window as the high-temperature characteristic value of each pixel window, and form a high-temperature distribution sequence of each pixel window with all high-temperature pixels in each pixel window;

[0017] Pixels with the absolute value of the difference between two temperature values ​​less than or equal to 2°C are divided into the same heat level. The heat run matrix of each high-temperature pixel in each pixel window is obtained by the same calculation method as the grayscale run matrix. The parameters of the heat run matrix include the total number of heat levels, the number of consecutive adjacent heat levels, and the search angle. Each row in the temperature run matrix of all high-temperature pixels in each search direction is used as the temperature run sequence of each heat level. The high temperature uniformity factor Ht of the i-th pixel window is i The expression is:

[0018]

[0019] In the formula, J i is the total number of high-temperature pixels in the i-th pixel window, a i,j , are respectively the temperature value of the jth high temperature pixel in the i-th pixel window and the high temperature characteristic value of the i-th pixel window, a i 、b i are the temperature sequence and high temperature distribution sequence of the ith pixel window, Her() is the function for calculating the Herfindahl index, Ent(b i ) is a function for calculating the two-dimensional Shannon entropy, exp[] is an exponential function with the natural constant e as the base, and ε is an adjustment parameter preset to be greater than 0;

[0020] Thermal resistance fuzzy factor Tr(θ) of the jth high-temperature pixel in the i-th pixel window in the search direction θ i,j The expression is:

[0021]

[0022] Where Ze(θ) i,j 、z(θ) i,j are the number of 0 elements in the temperature run matrix corresponding to the j-th high temperature pixel in the i-th pixel window in the search direction θ and the total number of elements in the temperature run matrix, respectively. (θ)' is the total number of heat levels of the jth high-temperature pixel in the i-th pixel window in the search direction θ, d(θ) i,j,β , d(θ) i,j,γare the temperature program sequences corresponding to the βth and γth heat levels of the jth high-temperature pixel in the i-th pixel window in the search direction θ, dtw[] is the DTW distance, e is a natural constant, and ε' is an adjustment parameter preset to be greater than 0;

[0023] Calculate the sum of the thermal resistance fuzzy factors of all high-temperature pixels in all search directions in each pixel window, calculate the reciprocal of the sum and the sum of the adjustment parameters preset to be greater than 0, and use the normalized value of the product of the reciprocal and the high-temperature uniformity factor of the corresponding pixel window as the conduction resistance coefficient of each pixel window.

[0024] Preferably, the solid phase firing sufficiency coefficient of each firing interval includes:

[0025] The conduction blocking coefficients of all pixels in the solid-phase firing infrared thermal imaging image at the initial moment of data acquisition are obtained by using a threshold segmentation algorithm to obtain each blocking characteristic pixel. For each firing interval, if the conduction blocking coefficient of the p-th blocking characteristic pixel at the t-th moment is greater than the conduction blocking coefficient at the t+1-th moment, then the t-th moment is recorded as the blocking decay moment of the p-th blocking characteristic pixel, and the difference between the conduction blocking coefficient of the p-th blocking characteristic pixel at the t-th moment and the conduction blocking coefficient at the t+1-th moment is taken as the blocking decay value at the t-th moment. All the blocking decay values ​​of the p-th blocking characteristic pixel in the corresponding firing interval are composed into a blocking decay sequence of the p-th blocking characteristic pixel in the corresponding firing interval, and all the blocking decay moments of the p-th blocking characteristic pixel in the corresponding firing interval are composed into a blocking decay moment sequence of the p-th blocking characteristic pixel in the corresponding firing interval.

[0026] The conduction blocking coefficient of each blocking characteristic pixel in each firing interval at all times is obtained by using the sequence decomposition algorithm to obtain the trend term intensity of each blocking characteristic pixel at each blocking decay moment. The sum of the trend term intensities of each blocking characteristic pixel in each firing interval at all blocking decay moments is taken as the blocking decay intensity of each blocking characteristic pixel in each firing interval. The heat conduction steady-state factor Rd of the pth blocking characteristic pixel in the nth firing interval is n,p The expression is:

[0027]

[0028] In the formula, δ n,p is the blocking decay intensity of the pth blocking characteristic pixel in the nth firing interval, Hr n,p,max is the maximum conduction blocking coefficient of the pth blocking characteristic pixel in the nth firing interval, T n,p is the total number of blocking decay moments of the pth blocking feature pixel in the nth firing interval, f n,p,t 、f n,p,minare respectively the blocking decay value of the p-th blocking characteristic pixel in the n-th firing interval at the t-th blocking decay moment and the minimum blocking decay value of the p-th blocking characteristic pixel in the n-th firing interval;

[0029] Calculate the Js divergence of the blocking decay time sequence of any blocking characteristic pixel and other blocking characteristic pixels in each firing interval, calculate the sum of the Js divergence and the adjustment parameter preset to be greater than 0, and use the ratio of the thermal conduction steady-state factor of any blocking characteristic pixel to the sum as the synergistic conduction factor of any blocking characteristic pixel in each firing interval;

[0030] The normalized value of the mean value of the cooperative conduction factor of all blocking characteristic pixels in each firing interval is taken as the solid phase firing sufficiency coefficient of each firing interval.

[0031] Preferably, the self-adaptive adjustment of the solid-phase firing reaction time according to the solid-phase firing sufficiency coefficient of each firing interval includes:

[0032] If the solid phase firing sufficiency coefficient of the firing interval is greater than or equal to the preset solid phase firing sufficiency threshold, the solid phase firing reaction duration is not adjusted; otherwise, the solid phase firing reaction duration is extended by a preset time.

[0033] In a second aspect, an embodiment of the present invention further provides a high-rate sodium iron phosphate positive electrode material, wherein the high-rate sodium iron phosphate positive electrode material is made by the steps of any one of the methods described above.

[0034] The present invention has at least the following beneficial effects:

[0035] The present invention obtains the conduction resistance coefficient through the temperature difference characteristics within the pixel neighborhood range in the solid phase firing image and the heat transfer obstruction characteristics within the high temperature pixel neighborhood range; comprehensively considers the temperature difference change status within the pixel neighborhood range, the distribution position status of the high temperature pixel and the uniformity of heat transfer, and makes a more accurate assessment of the heat conduction resistance status within the pixel neighborhood range; obtains the solid phase firing sufficiency coefficient based on the conduction resistance coefficient decay characteristics of the blocking characteristic pixels in the firing interval based on the time series and the similarity characteristics of the conduction resistance decay moments, and considers the blocking characteristic pixels in the firing interval to obtain the conduction resistance coefficient. On the basis of stable and smooth heat conduction in the firing interval, the synergistic change analysis caused by the sufficient solid-phase firing of the mixture is added, which more accurately reflects the degree of sufficient solid-phase firing of the mixture; the sufficient solid-phase firing reaction of the mixture is judged according to the solid-phase firing sufficiency coefficient of the real-time firing interval, and the solid-phase firing reaction time of the mixture is adaptively adjusted to obtain a more accurate solid-phase firing reaction time, avoiding the solid-phase firing reaction time of the mixture being too long or too short, which affects the cycle performance and rate performance of the titanium-based fast ion conductor modified sodium iron phosphate positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 A flowchart of a method for preparing a high-rate sodium iron phosphate positive electrode material provided by one embodiment of the present invention;

[0038] Figure 2 It is a schematic diagram of thermal imaging image acquisition during solid phase sintering of mixed materials;

[0039] Figure 3 This is a process flow chart for preparing sodium iron phosphate positive electrode materials;

[0040] Figure 4 This is a schematic diagram of the temperature range window of high-temperature pixels. DETAILED DESCRIPTION

[0041] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a high-rate sodium iron phosphate positive electrode material and preparation method proposed in accordance with the present invention, its specific implementation method, structure, characteristics and effects, in combination with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "another embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0042] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.

[0043] The specific scheme of a high-rate sodium iron phosphate positive electrode material and a preparation method provided by the present invention is described in detail below with reference to the accompanying drawings.

[0044] Example 1 provides a method for preparing a high-rate sodium iron phosphate positive electrode material. For the preparation flow chart, please refer to Figure 1 , the specific preparation process is as follows:

[0045] Example 1

[0046] (1) 32 g of PEG-6000 flake particles were dissolved in 2 L of ultrapure water and mechanically stirred for 5 min. Then, 754.1 g of iron phosphate, 10.3 g of anatase titanium dioxide, 23.2 g of sodium dihydrogen phosphate and 272.9 g of sodium carbonate powder were added in sequence to obtain a mixed solution.

[0047] (2) The mixed solution was sheared and dispersed at 1000 rpm for 30 min to obtain a slurry, and then the slurry was transferred to a sand mill for grinding. The grinding medium was a zirconia ball with a diameter of 0.1-0.2 mm. The grinding line speed was set to 15 m / s and the grinding time was set to 4 h to obtain a mixed slurry with a median particle size D50 of 80-200 nm. In this embodiment, the solid content of the mixed slurry was 30%.

[0048] (3) The mixed slurry obtained in step (2) is spray dried. In this embodiment, the feed port temperature is set to 240°C, the discharge port temperature is set to 100°C, and the median particle size of the spray particles is 6-8μm; the spray-dried mixed material is evenly placed in a nitrogen-protected box furnace, and solid-phase sintered at 800°C for 8-12h. The temperature rise rate during the solid-phase sintering reaction is 2°C / min. After the reaction product is cooled, it is processed through a 150-mesh sieve to obtain a titanium-based fast ion conductor modified sodium iron phosphate positive electrode material. During the solid-phase sintering reaction of the mixed material, the following steps are used to adjust the solid-phase sintering time, specifically:

[0049] Step S001, collecting infrared thermal imaging images during the preparation process of the titanium-based fast ion conductor modified sodium iron phosphate positive electrode material and performing preprocessing.

[0050] The infrared thermal imager is used to collect the infrared thermal imaging image of the solid phase firing of the mixed material in the preparation process of the titanium-based fast ion conductor modified sodium iron phosphate positive electrode material. The specific collection method is: the infrared thermal imager is placed directly above the center of the nitrogen protection box furnace. After the mixed material is solid-phase fired for 8 hours, the infrared thermal imaging image is collected at a top-down angle. The collection time interval is 5s. The implementer can set the time interval according to the actual situation. This embodiment does not limit this. In order to prevent the noise interference in the obtained infrared thermal imaging image of the solid phase firing of the mixed material from being too serious and affecting the subsequent analysis, a bilateral filtering algorithm is used to denoise the infrared thermal imaging image. On the basis of removing the noise, the detailed information in the image is retained as much as possible. Since the infrared thermal imaging data collection method and the bilateral filtering algorithm are both existing well-known technologies, the specific acquisition process will not be repeated. The implementer can select other algorithms according to the actual situation to perform denoising preprocessing on the thermal imaging image of the solid phase firing of the mixed material.

[0051] For the convenience of subsequent description, the solid-phase firing thermal imaging image of the mixed material is recorded as a solid-phase firing diagram. At this point, a solid-phase firing diagram based on a time series can be obtained. The schematic diagram of the acquisition of the solid-phase firing thermal imaging image of the mixed material is shown in FIG. Figure 2 shown.

[0052] Step S002, obtaining the conduction resistance coefficient through the temperature difference characteristics within the pixel neighborhood range in the solid phase firing image and the heat transfer obstruction characteristics within the high temperature pixel neighborhood range; obtaining the solid phase firing sufficiency coefficient based on the conduction resistance coefficient decay characteristics of the blocking characteristic pixels in the firing interval based on the time series and the similarity characteristics of the conduction resistance decay moments.

[0053] Specifically, this embodiment first collects solid-phase firing infrared thermal imaging images at each moment during the solid-phase firing reaction; constructs a pixel window with each pixel in the image as the center; obtains the conduction resistance coefficient of each pixel window according to the distribution characteristics of the temperature value of each pixel in each pixel window; the solid-phase firing reaction process is evenly divided into various firing intervals; the solid-phase firing sufficiency coefficient of each firing interval is obtained according to the conduction resistance coefficient of each pixel window and the temperature change characteristics of the pixels at different moments in each firing interval; the adaptive adjustment of the solid-phase firing reaction time is completed according to the solid-phase firing sufficiency coefficient of each firing interval. The specific process flow chart of the preparation process of sodium iron phosphate positive electrode material is as follows: Figure 3 The construction process of the solid phase firing sufficiency coefficient of each firing interval is as follows:

[0054] In the preparation process of titanium-based fast ion conductor modified sodium iron phosphate positive electrode material, the more complete the solid-phase sintering reaction of the mixed material, the higher the uniformity of the temperature distribution of the material, and the larger the proportion of the peak temperature area; secondly, the more complete the solid-phase sintering reaction of the mixed material, the better the thermal conductivity of the material usually is, which is specifically manifested in the solid-phase sintering diagram as the absence of obvious thermal resistance areas, blurred texture characteristics, and heat can be quickly transferred inside the material.

[0055] Take the i-th pixel in the solid phase sintering diagram at the tth moment as an example for subsequent analysis, build a pixel window with the i-th pixel as the center, the size of the pixel window is 9×9, and take the sequence of the temperature values ​​of all pixels in the i-th pixel window in ascending order as the temperature sequence a of the i-th pixel window i , calculate the third quartile α(3) of the temperature series of the i-th pixel window i , all temperature values ​​in the i-th pixel window are greater than or equal to α(3) i The pixel is recorded as the high temperature pixel of the i-th pixel window, and the temperature mean of all high temperature pixels in the i-th pixel window is recorded as the high temperature characteristic value of the i-th pixel window; the position coordinates of all high temperature pixels in the i-th pixel window are sequenced in ascending order of the horizontal axis and the vertical axis as the high temperature distribution sequence b of the i-th pixel window. i .

[0056] A temperature run window is constructed with each high-temperature pixel in the i-th pixel window as the center. The size of the temperature run window is 5×5. The heat run matrix c of all high-temperature pixels in the i-th pixel window is obtained by constructing the grayscale run matrix. For example, the heat run matrix c of the j-th high-temperature pixel in the i-th pixel window is i,j =(β,l,θ), where β is the total number of heat levels of the pixel. Since the heating rate during the solid-phase sintering reaction of the mixed material in this embodiment is 2°C / min, the pixels whose absolute value of the difference between two temperature values ​​is less than or equal to 2°C are classified as the same heat level; l is the number of consecutive adjacent heat levels. Since the temperature run window size is 5×5, the maximum value of l in this embodiment is 5; θ is the search angle, which is fixed to the eight-neighborhood direction of the high-temperature pixel in this embodiment. The schematic diagram of the temperature run window of the high-temperature pixel is as follows: Figure 4 Each row in the temperature run matrix of all high-temperature pixels in each search direction is used as a temperature run sequence d of a heat level. Since the construction method of the grayscale run matrix is ​​an existing well-known technology, the specific acquisition process will not be described in detail.

[0057] Based on the above analysis, this embodiment constructs a conduction resistance coefficient to characterize the degree of heat transfer resistance within the pixel neighborhood, and the expression is:

[0058]

[0059]

[0060]

[0061] Where Ht i is the high temperature uniformity factor of the i-th pixel window, J i is the total number of high-temperature pixels in the i-th pixel window, a i,j , are respectively the temperature value of the jth high temperature pixel in the i-th pixel window and the high temperature characteristic value of the i-th pixel window, a i 、b i are the temperature sequence and high temperature distribution sequence of the ith pixel window, Her() is the function for calculating the Herfindahl index, Ent(b i ) is a function for calculating two-dimensional Shannon entropy, exp[] is an exponential function with the natural constant e as the base, ε is an adjustment parameter preset to be greater than 0 to prevent the denominator from being 0. In this embodiment, ε=1, and the implementer can set it according to the actual situation, and this embodiment does not limit this;

[0062] Tr(θ) i,j is the thermal resistance fuzzy factor of the jth high-temperature pixel in the i-th pixel window in the search direction θ, Ze(θ)i,j 、z(θ) i,j are the number of 0 elements in the temperature run matrix corresponding to the j-th high temperature pixel in the i-th pixel window in the search direction θ and the total number of elements in the temperature run matrix, respectively. (θ)' is the total number of heat levels of the jth high-temperature pixel in the i-th pixel window in the search direction θ, d(θ) i,j,β , d(θ) i,j,γ are the temperature sequence corresponding to the βth and γth heat levels of the jth high-temperature pixel in the i-th pixel window in the search direction θ, dtw[] is the DTW distance, e is a natural constant, ε' is an adjustment parameter preset to be greater than 0 to prevent the denominator from being 0, and in this embodiment, ε'=1, which can be set by the implementer according to the actual situation, and this embodiment does not limit this;

[0063] hr i is the conduction block coefficient of the i-th pixel window; θ' is the total number of search directions of the temperature run matrix, in this embodiment, θ'=8, norm[] is the normalization function, so that Hr i The value range of is in the range of [0,1], ∈” is an adjustment parameter preset to be greater than 0 to prevent the denominator from being 0. In this embodiment, ∈”=1, and the implementer can set it according to the actual situation, and this embodiment does not impose any restrictions on this.

[0064] When the difference between the temperature values ​​of all high-temperature pixels in the i-th pixel window and the high-temperature characteristic value of the i-th pixel window is smaller, that is, The smaller the Herfindahl index is, the smaller the temperature difference between all high-temperature pixels in the ith pixel window is. At the same time, when the Herfindahl index of the temperature sequence corresponding to the ith pixel window is smaller, that is, Her(a i ) is smaller, indicating that the temperature distribution of all pixels in the ith pixel window is more uniform; at the same time, when the two-dimensional Shannon entropy of the high temperature distribution sequence corresponding to the ith pixel window is larger, that is, Ent(b i ) is larger, indicating that the position distribution of all high-temperature pixels in the ith pixel window is more discrete, the uniform distribution of high-temperature points in the ith pixel window is more significant, and the high-temperature uniformity factor Hti of the ith pixel window is larger.

[0065] When the proportion of zero elements in the temperature run matrix corresponding to the j-th high-temperature pixel in the i-th pixel window in the search direction θ is smaller, that is, The smaller it is, the lower the possibility that there are more heat levels in the neighborhood of the j-th high-temperature pixel; at the same time, when the difference between the temperature program sequences corresponding to all heat levels of the j-th high-temperature pixel in the search direction θ in the i-th pixel window is smaller, that is, The smaller it is, the smaller the difference between the run distances of different heat levels in the neighborhood of the j-th high-temperature pixel is, and the temperature in the neighborhood of the j-th high-temperature pixel is evenly distributed, making the phenomenon of heat transfer obstruction less obvious. The thermal resistance fuzzy factor Tr(θ) i,j The bigger.

[0066] When the high temperature uniformity factor of the i-th pixel window is smaller, that is, Ht i The smaller it is, the more uneven the temperature distribution in the neighborhood of the ith pixel in the solid-phase firing diagram at the tth moment is; at the same time, when the sum of the thermal resistance fuzzy factors of all high-temperature pixels in the ith pixel window in all search directions is smaller, that is, The smaller it is, the more significant the heat transfer obstruction phenomenon of all high-temperature pixels in the neighborhood of the ith pixel in the solid-phase firing image at the tth moment in all search directions is. Furthermore, the more significant the heat conduction obstruction phenomenon caused by insufficient solid-phase firing of the mixed material in the neighborhood of the ith pixel in the solid-phase firing image at the tth moment is, the greater the conduction retardation coefficient Hr. i The bigger.

[0067] The conduction block coefficient of each pixel window is assigned to the central pixel of the corresponding pixel window. So far, the conduction block coefficient of the i-th pixel in the solid-phase firing image at all times can be obtained according to the above method. The sequence of conduction block coefficients of all pixels in the solid-phase firing image at the initial moment of data acquisition, that is, the first moment after the mixed material is solid-phase fired for 8 hours, is recorded in ascending order as the conduction block sequence of the solid-phase firing image at the initial moment of data acquisition, and is used as input. The segmentation threshold L of the conduction block sequence is obtained using the Otsu method OTSU, and all pixels with conduction block coefficients greater than or equal to L are recorded as block feature pixels.

[0068] Set every 30 minutes as a firing interval, and take the nth firing interval as an example for subsequent analysis. In the nth firing interval, if the conduction blocking coefficient of the pth blocking feature pixel at the tth moment is greater than the conduction blocking coefficient at the t+1th moment, then the tth moment is recorded as the blocking decay moment of the blocking feature pixel, and the difference between the conduction blocking coefficient of the pth blocking feature pixel at the tth moment and the conduction blocking coefficient at the t+1th moment is taken as the blocking decay value at the tth moment, and the sequence composed of all the blocking decay values ​​of the pth blocking feature pixel in the nth firing interval in ascending order of time sequence is taken as the blocking decay sequence f of the pth blocking feature pixel in the nth firing interval. n,p The sequence of all the blocking decay moments of the pth blocking characteristic pixel in the nth firing interval in ascending order of time sequence is recorded as the blocking decay moment sequence g of the pth blocking characteristic pixel n,p .

[0069] The conduction block coefficient of the pth blocking characteristic pixel in the nth firing interval at all times is taken as input, and the STL (Seasonal-Trend decomposition using LOESS) sequence decomposition algorithm is used to obtain the trend term intensity of the pth blocking characteristic pixel in the nth firing interval at each blocking decay moment. The sum of the trend term intensities of all blocking decay moments of the pth blocking characteristic pixel in the nth firing interval is recorded as the blocking decay intensity δ of the pth blocking characteristic pixel in the nth firing interval. n,p Since the STL sequence decomposition algorithm is a well-known technology, the specific acquisition process will not be described in detail in this embodiment.

[0070] Based on the above analysis, the solid-phase firing sufficiency coefficient is constructed in this embodiment to characterize the sufficiency of the solid-phase firing reaction of the mixed material in the firing interval, and the expression is:

[0071]

[0072]

[0073]

[0074] In the formula, Rd n,p is the heat conduction steady-state factor of the pth blocking characteristic pixel in the nth firing interval, δ n,p is the blocking decay intensity of the pth blocking characteristic pixel in the nth firing interval, Hr n,p,max is the maximum conduction blocking coefficient of the pth blocking characteristic pixel in the nth firing interval, T n,p is the total number of blocking decay moments of the pth blocking feature pixel in the nth firing interval, f n,p,t 、f n,p,min are respectively the blocking decay value of the p-th blocking characteristic pixel in the n-th firing interval at the t-th blocking decay moment and the minimum blocking decay value of the p-th blocking characteristic pixel in the n-th firing interval, ∈ is an adjustment parameter preset to be greater than 0 to prevent the denominator from being 0. In this embodiment, ∈=1, and the implementer can set it according to the actual situation, and this embodiment does not limit this;

[0075] Cf n,p is the synergistic conduction factor of the pth blocking characteristic pixel in the nth firing interval, P n is the total number of blocking characteristic pixels in the nth firing interval, g n,p , g n,qare the blocking decay time sequences corresponding to the pth and qth blocking characteristic pixels in the nth firing interval, respectively; Js() is a function for calculating the Js divergence; ∈' is an adjustment parameter preset to be greater than 0 to prevent the denominator from being 0; in this embodiment, ∈'=1, and the implementer can set it according to the actual situation, and this embodiment does not limit this;

[0076] S n is the solid phase sintering sufficiency coefficient of the nth sintering interval, norm[] is the normalization function, so that Sf n The value range of is in the range of [0,1].

[0077] When the blocking decay intensity of the pth blocking characteristic pixel in the nth firing interval is larger, that is, δ n,p The larger the value is, the greater the trend of the conduction blocking coefficient of the pth blocking characteristic pixel in the nth firing interval is, and the more stable the heat conduction of the pth blocking characteristic pixel in the nth firing interval is; at the same time, when the maximum conduction blocking coefficient of the pth blocking characteristic pixel in the nth firing interval is smaller, that is, Hr n,p,max The smaller it is, the less the heat conduction obstruction caused by insufficient solid-phase sintering of the mixed material in the neighborhood of the p-th blocking characteristic pixel in the n-th firing interval is; at the same time, when the difference between the blocking decay value of the p-th blocking characteristic pixel in the n-th firing interval at all blocking decay moments and the minimum blocking decay value is greater, that is, The larger the value, the more significant the situation that the heat conduction obstruction of the p-th blocking characteristic pixel in the n-th firing interval becomes milder. Furthermore, the more significant the situation that the heat conduction of the p-th blocking characteristic pixel in the n-th firing interval is stable and smooth, Rd n,p The bigger.

[0078] When the heat conduction steady-state factor of the pth blocking characteristic pixel in the nth firing interval is larger, that is, Rd n,p The larger the value, the more significant the stable and smooth heat conduction of the pth blocking feature pixel in the nth firing interval; at the same time, when the sum of the Js divergences between the pth blocking feature pixel and the corresponding blocking decay time series of all other blocking feature pixels in the nth firing interval is smaller, that is, The smaller it is, the more similar the situation in which the heat conduction obstruction phenomenon in the neighborhood of the pth blocking characteristic pixel in the nth firing interval is to that in the neighborhood of the other blocking characteristic pixels. Furthermore, the situation in which the heat conduction obstruction in the neighborhood of the pth blocking characteristic pixel in the nth firing interval is lighter is more likely to be a synergistic effect caused by sufficient solid phase firing of the mixed materials. The synergistic conduction factor Cf n,p The bigger.

[0079] When the sum of the synergistic conduction factors of all blocking characteristic pixels in the nth firing interval is smaller, that is, The smaller it is, the less significant the stable and smooth heat conduction in the nth firing interval is, and the less likely it is that the solid-phase firing reaction of the mixture is sufficient. At this time, the solid-phase firing reaction time of the mixture should be extended to make the solid-phase firing reaction of the mixture tend to a sufficient state, so as to avoid affecting the electrochemical activity and stability of the subsequently prepared titanium-based fast ion conductor modified sodium iron phosphate positive electrode material.

[0080] At this point, the solid phase firing sufficiency coefficient of each firing interval can be obtained in real time according to the above method.

[0081] Step S003, judging the sufficiency of the solid phase firing reaction of the mixed material according to the solid phase firing sufficiency coefficient of the real-time firing interval, and adaptively adjusting the solid phase firing reaction duration of the mixed material.

[0082] Set a sufficient solid-phase firing threshold value W. When the sufficient solid-phase firing coefficient of the real-time firing interval is greater than or equal to the sufficient solid-phase firing threshold value W, it indicates that the solid-phase firing reaction of the mixed material in the corresponding firing interval has reached a sufficient state, and there is no need to adjust the solid-phase firing reaction duration of the mixed material; when the sufficient solid-phase firing coefficient of the real-time firing interval is less than the sufficient solid-phase firing threshold value W, it indicates that the solid-phase firing reaction of the mixed material in the corresponding firing interval has not reached a sufficient state, and the solid-phase firing reaction duration of the mixed material needs to be extended by Vmin. In this embodiment, the sufficient solid-phase firing threshold value W = 0.7, and the value range of W is [0,1]. The larger W is, the stricter the requirement for the sufficient solid-phase firing of the mixed material. In this embodiment, V = 30. The implementer can set the sufficient solid-phase firing threshold value and the value of V according to the actual situation.

[0083] At this point, the solid-phase sintering reaction time of the mixed material can be adaptively adjusted according to the above method to obtain a titanium-based fast ion conductor modified sodium iron phosphate positive electrode material with sufficient solid-phase sintering.

[0084] After testing, the specific surface area of ​​the titanium-based fast ion conductor modified sodium iron phosphate positive electrode material prepared according to the method in this embodiment is 7.65m 2 / g, median particle size is 7-9μm, tap density is 1.2g / cm 3 .

[0085] Finally, the CE2430 battery prepared with titanium-based fast ion conductor modified sodium iron phosphate positive electrode material as raw material was used as an example to test the battery performance. The specific process is as follows:

[0086] Titanium-based fast ion conductor modified sodium iron phosphate positive electrode material, PVDF polyvinylidene fluoride and Super P conductive agent were mixed in a mass ratio of 80:10:10, dissolved and dispersed evenly with N-methylpyrrolidone, coated on aluminum foil, dried and rolled to make a working electrode, with metal sodium sheet as electrode and reference electrode, 1 mol / LNaPF6 solution as electrolyte, the solute of the electrolyte was EC ethylene carbonate, DMC dimethyl carbonate and EMC methyl ethyl carbonate in a volume ratio of 1:1:1, Whatman glass fiber as diaphragm, assembled into CE2430 type battery in a glove box, the assembled battery was activated by 1C current cycle for 5 cycles, the charge and discharge range was set to 2.0-4.5V, and then cycled for 5 cycles at 1C current, and then cycled for 5 cycles at 2C, 3C, 5C, and 10C currents, and then restored to 1C current for 5 cycles, and the 10C / 1C retention rate results are shown in the test results of Table 1.

[0087] Table 1 Test results

[0088]

[0089] It can be seen from Table 1 that the battery prepared by this embodiment has good cycle performance and high rate performance. Thus, a high rate sodium iron phosphate positive electrode material and preparation method are realized.

[0090] Based on the same inventive concept as the above method, an embodiment of the present invention also provides a high-rate sodium iron phosphate positive electrode material, which is made by the steps of any one of the above-mentioned methods for preparing a high-rate sodium iron phosphate positive electrode material.

[0091] In summary, the embodiment of the present invention judges the sufficiency of the solid-phase sintering reaction of the mixed material according to the solid-phase sintering sufficiency coefficient of the real-time sintering interval, and adaptively adjusts the solid-phase sintering reaction time of the mixed material to obtain a more accurate solid-phase sintering reaction time, thereby avoiding the solid-phase sintering reaction time of the mixed material being too long or too short, which affects the cycle performance and rate performance of the titanium-based fast ion conductor modified sodium iron phosphate positive electrode material.

[0092] It should be noted that the sequence of the above embodiments of the present invention is only for description and does not represent the advantages and disadvantages of the embodiments. The above is a description of a specific embodiment of this specification. In addition, the processes depicted in the accompanying drawings do not necessarily require the specific order or continuous order shown to achieve the desired results. In some embodiments, multitasking and parallel processing are also possible or may be advantageous.

[0093] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-rate sodium iron phosphate positive electrode material, characterized in that: The method comprises the following steps: (1) dissolving PEG-6000 flake particles in ultrapure water, stirring, and sequentially adding iron phosphate, anatase titanium dioxide, sodium dihydrogen phosphate, and sodium carbonate powder to obtain a mixed solution; (2) The mixed solution was sheared and dispersed at 1000 rpm for 30 min, and then transferred to a sand mill for grinding to obtain a mixed slurry; (3) spray drying the mixed slurry, and then placing it in a nitrogen-protected box furnace for solid-phase sintering reaction, and after the reaction product is cooled, refining treatment is performed to obtain a titanium-based fast ion conductor modified sodium iron phosphate positive electrode material; collecting solid-phase sintering infrared thermal imaging images at each moment in the solid-phase sintering reaction process; constructing a pixel window with each pixel in the image as the center; obtaining the conduction resistance coefficient of each pixel window according to the distribution characteristics of the temperature value of each pixel in each pixel window; evenly dividing the solid-phase sintering reaction process into various sintering intervals; obtaining the solid-phase sintering sufficiency coefficient of each sintering interval according to the conduction resistance coefficient of each pixel window and the temperature change characteristics of the pixels at different moments in each sintering interval; completing the adaptive adjustment of the solid-phase sintering reaction time according to the solid-phase sufficiency coefficient of each sintering interval; The method of obtaining the conduction resistance coefficient of each pixel window according to the distribution characteristics of the temperature value of each pixel in each pixel window includes: Arrange the temperature values ​​of all pixels in each pixel window in ascending order as the temperature sequence of each pixel window, take the pixels in the pixel window whose temperature values ​​are greater than or equal to the third quartile of the temperature sequence as the high-temperature pixels of the pixel window, take the mean value of all high-temperature pixels in each pixel window as the high-temperature characteristic value of each pixel window, and form a high-temperature distribution sequence of each pixel window with all high-temperature pixels in each pixel window; Pixels with the absolute value of the difference between two temperature values ​​less than or equal to 2°C are divided into the same heat level. The heat run matrix of each high-temperature pixel in each pixel window is obtained by the same calculation method as the grayscale run matrix. The parameters of the heat run matrix include the total number of heat levels, the number of consecutive adjacent heat levels, and the search angle. Each row in the temperature run matrix of all high-temperature pixels in each search direction is used as the temperature run sequence of each heat level. The high temperature uniformity factor of the i-th pixel window is The expression is: In the formula, is the total number of high-temperature pixels in the i-th pixel window, , are respectively the temperature value of the jth high temperature pixel in the i-th pixel window and the high temperature characteristic value of the i-th pixel window. , are the temperature sequence and high temperature distribution sequence of the i-th pixel window, respectively. To calculate the function of the Herfindahl index, is the function for calculating the two-dimensional Shannon entropy, exp[] is an exponential function with the natural constant e as the base, It is an adjustment parameter preset to be greater than 0; The jth high temperature pixel in the i-th pixel window is in the search direction Thermal resistance fuzziness factor The expression is: In the formula, , are the jth high temperature pixel in the i-th pixel window in the search direction The number of 0 elements in the corresponding temperature run matrix and the total number of elements in the corresponding temperature run matrix. is the jth high temperature pixel in the i-th pixel window in the search direction The total number of heat levels on , are the jth high temperature pixel in the i-th pixel window in the search direction Previous , The temperature program sequence corresponding to each heat level, is the DTW distance, is a natural constant, It is an adjustment parameter preset to be greater than 0; Calculate the sum of the thermal resistance fuzzy factors of all high-temperature pixels in all search directions in each pixel window, calculate the reciprocal of the sum and the sum of the adjustment parameters preset to be greater than 0, and use the normalized value of the product of the reciprocal and the high-temperature uniformity factor of the corresponding pixel window as the conduction resistance coefficient of each pixel window.

2. The method for preparing a high-rate sodium iron phosphate positive electrode material according to claim 1, characterized in that: In the process of obtaining the mixed solution, the mass ratio of PEG-6000, ultrapure water, iron phosphate, anatase titanium dioxide, sodium dihydrogen phosphate, and sodium carbonate powder is 1:62.5:23.57:0.32:0.725:8.

53.

3. The method for preparing a high-rate sodium iron phosphate positive electrode material according to claim 1, characterized in that: The grinding medium is a zirconia ball with a diameter of 0.1-0.2 mm, the grinding linear speed is 15 m / s, the grinding time is 4 hours, and a mixed slurry with a median particle size D50 of 80-200 nm is obtained.

4. The method for preparing a high-rate sodium iron phosphate positive electrode material according to claim 1, characterized in that: The spray drying comprises: The feed inlet temperature is 240°C, the discharge port temperature is 100°C, and the median particle size of the spray particles is 6-8 μm.

5. The method for preparing a high-rate sodium iron phosphate positive electrode material according to claim 1, characterized in that: The solid phase sintering reaction comprises: solid phase sintering at 800° C. for 8-12 hours, and the temperature rising rate during the solid phase sintering reaction is 2° C. / min.

6. The method for preparing a high-rate sodium iron phosphate positive electrode material according to claim 1, characterized in that: The refinement treatment is to pass through a 150-mesh sieve, and the specific surface area of ​​the titanium-based fast ion conductor modified sodium iron phosphate positive electrode material is 7.65 , the median particle size is 7~9 , the tap density is 1.2 .

7. The method for preparing a high-rate sodium iron phosphate positive electrode material according to claim 1, characterized in that: The solid phase firing sufficiency coefficient of each firing interval includes: The conduction blocking coefficients of all pixels in the solid-phase firing infrared thermal imaging image at the initial moment of data acquisition are obtained by using a threshold segmentation algorithm to obtain each blocking characteristic pixel. For each firing interval, if the conduction blocking coefficient of the p-th blocking characteristic pixel at the t-th moment is greater than the conduction blocking coefficient at the t+1-th moment, then the t-th moment is recorded as the blocking decay moment of the p-th blocking characteristic pixel, and the difference between the conduction blocking coefficient of the p-th blocking characteristic pixel at the t-th moment and the conduction blocking coefficient at the t+1-th moment is taken as the blocking decay value at the t-th moment. All the blocking decay values ​​of the p-th blocking characteristic pixel in the corresponding firing interval are composed into a blocking decay sequence of the p-th blocking characteristic pixel in the corresponding firing interval, and all the blocking decay moments of the p-th blocking characteristic pixel in the corresponding firing interval are composed into a blocking decay moment sequence of the p-th blocking characteristic pixel in the corresponding firing interval. The conduction blocking coefficient of each blocking characteristic pixel in each firing interval at all times is obtained by using the sequence decomposition algorithm to obtain the trend term intensity of each blocking characteristic pixel at each blocking decay moment. The sum of the trend term intensities of each blocking characteristic pixel in each firing interval at all blocking decay moments is taken as the blocking decay intensity of each blocking characteristic pixel in each firing interval. The heat conduction steady-state factor of the pth blocking characteristic pixel in the nth firing interval is The expression is: In the formula, is the blocking decay intensity of the pth blocking feature pixel in the nth firing interval, is the maximum conduction blocking coefficient of the pth blocking characteristic pixel in the nth firing interval, is the total number of blocking decay moments of the pth blocking feature pixel in the nth firing interval, , are respectively the blocking decay value of the p-th blocking characteristic pixel in the n-th firing interval at the t-th blocking decay moment and the minimum blocking decay value of the p-th blocking characteristic pixel in the n-th firing interval; Calculate the Js divergence of the blocking decay time sequence of any blocking characteristic pixel and other blocking characteristic pixels in each firing interval, calculate the sum of the Js divergence and the adjustment parameter preset to be greater than 0, and use the ratio of the thermal conduction steady-state factor of any blocking characteristic pixel to the sum as the synergistic conduction factor of any blocking characteristic pixel in each firing interval; The normalized value of the mean value of the cooperative conduction factor of all blocking characteristic pixels in each firing interval is taken as the solid phase firing sufficiency coefficient of each firing interval.

8. The method for preparing a high-rate sodium iron phosphate positive electrode material according to claim 1, characterized in that: The self-adaptive adjustment of the solid-phase firing reaction time according to the solid-phase firing sufficiency coefficient of each firing interval includes: If the solid phase firing sufficiency coefficient of the firing interval is greater than or equal to the preset solid phase firing sufficiency threshold, the solid phase firing reaction duration is not adjusted; otherwise, the solid phase firing reaction duration is extended by a preset time.

9. A high-rate sodium iron phosphate positive electrode material, characterized in that: The high-rate sodium iron phosphate positive electrode material is made by the method described in any one of claims 1-8.

Citation Information

Patent Citations

  • Titanium-based fast ion conductor modified sodium ferric phosphate positive electrode material, preparation method thereof and battery prepared from positive electrode material

    CN114824205A